Acute-Onset Vitreous Hemorrhage of Unknown Origin before Vitrectomy: Causes and Prognosis - Dong Yoon Kim; Soo Geun Joe; Seunghee Baek; June-Gone Kim; Young Hee Yoon; Joo Yong Lee (Journal of Ophthalmology, 2015)
Purpose. To analyze causes and prognosis of acute-onset preoperatively unknown origin vitreous hemorrhage (VH). Methods. This study included patients who underwent vitrectomy for acute-onset preoperatively unknown origin VH. The underlying causes of VH, which were identified after vitrectomy, were analyzed. And overall visual prognosis of unknown origin VH was analyzed. Risk scoring system was developed to predict visual prognosis after vitrectomy. Results. 169 eyes were included. Among these, retinal vein occlusion (RVO), retinal break, and age-related macular degeneration (AMD) were identified in 74 (43.8%), 50 (29.6%), and 21 (12.4%) patients, respectively. After vitrectomy, logMAR BCVA significantly improved from 1.93±0.59 to 0.47±0.71. However, postoperative BCVA in AMD eyes were significantly poorer than others. Poor visual prognosis after vitrectomy was associated with old age, poor preoperative vision in both eyes, and drusen in the fellow eye. Conclusions. RVO, retinal break, and AMD are the most common causes of acute-onset preoperatively unknown origin VH and the most common causes of VH change with age. The visual prognosis of unknown origin VH is relatively good, except among AMD patients. Older patients with poor preoperative BCVA in both eyes and patients with AMD in the fellow eye are at a higher risk of poor visual prognosis following vitrectomy.